Adaptive anti-jamming scheme based on meta-surface antenna - GUO Yuze; JIN Liang; XU Xiaoming; MA Keming; PEI Chen (Dianxin kexue)
Aiming at the problem that traditional anti-jamming schemes cannot choose suitable anti-jamming strategies according to different types of jamming forms, an adaptive anti-jamming scheme based on meta-surface antenna was proposed. According to the incident direction of the expected signal and the jamming signal, the type of jamming was determined and the targeted anti-jamming scheme was formulated. Firstly, an improved sparsity adaptive matching pursuit (SAMP) algorithm was designed to estimate the direction of arrival (DOA). The multi-dimensional observation capability of meta-surface antenna could be used to estimate the source number and DOA of coherent signal sources with high precision under little snapshot sampling. Secondly, the DOA information of the signal was used to judge the existence of main-lobe interference and sidelobe interference, while the corresponding anti-jamming strategy was selected. When the main-lobe jamming existing, the multi-dimensional observation capability of the meta-surface antenna was used to configure the improved blocking matrix preprocessing structure on the antenna to achieve the main-lobe jamming suppression. When side-lobe jamming existing, a quadratic inequality linear power minimization algorithm was used to realize anti jamming. When two jamming forms exist at the same time, blocking matrix and beamforming were used to resist jamming. The simulation results show that the proposed scheme has better signal interference noise ratio (SINR) improvement for different jamming types. When both main-lobe and side-lobe jamming exist, the gain can be improved by up to 6 dB compared with the traditional scheme.